Potential Development Of Spiritual Tourism In Kampung Budaya Sindangbarang, Bogor - Seruni Dinitri (Program Studi Hospitality dan Pariwisata, 2018)
ABSTRACTKampung Budaya Sindangbarang is one of tourism destination in Bogor Regency that has a beautiful landscape, high cultural value, and the discovery of historical sites around it. The purpose of this research is to find out the potency to develop spiritual tourism in Sindangbarang Cultural Village. This research uses a descriptive method with quantitave approach. Primary data were obtained through interview with the management of Sindangbarang Cultural Village, questionnaire distribution and also direct observation. For secondary data obtained through data from the Bogor Regency Tourism Office, the Central Statistics Agency, documentations of Sindangbarang Cultural Village, other relevant institutions, journals and other supporting books. Variables used to see the potency to develop spiritual tourism using Spiritual Element theory (Pechlaner in Conrady, 2011) with dimensions of attraction, places and motives. Based on the results of the analysis found that elements of spiritual tourism in the form of attraction, places and motives can become the strength of Sindangbarang Cultural Village in developing spiritual tourism.Keyword: Potency of Development, Spiritual Tourism, Kampung Budaya Sindangbarang